CONTROL MICROBIOLÓGICO SOBRE Streptococcus Mutans Y SU ACCIÓN ACIDOGÉNICA - Gamboa, Fredy; Departamento de Microbiología (Facultad de Ciencias) y Centro de Investigaciones Odontológicas (Facultad de Odontología). Pontificia Universidad Javeriana, Bogotá (Pontificia Universidad Javeriana, 2004)
The actions made by health institutions in the prevention and control of dental caries have not been enough to achieve an important reduction of this disease. At the present moment, the microbiological control or replacement therapy applied for the prevention of the infectious diseases is just a hypothetical possibility. However, it is important to study and analyze the real value that this strategie can have in the future as a way to control dental problems, specifically dental caries. This therapeutical possibility acquires more importance with the awareness that preventive measures taken at the present time don’t have the expected impact. The goal of this article is to present an analysis of the researches made in  the search, improvement and  application of Streptococcus mutans  strains in the microbiological  control on S. mutans native strains and thus, the prevention of dental  caries. In the history of the studies made in microbiological control, the  works made by Hillman et al with of S. mutans mutant strains, JH1001, JH1005, JH1140 and BCS3-L1 were distinguished. In this group of  strains, the genetic stability and also the capacity to colonize and stay  on the oral cavity and other important characteristics of its use on microbiological control were evaluated. The  advances obtained in these works in conjunction with the availability of more efficient techniques of  genetic engineering allow to think that the achievement of the perfect strain for prevention of dental caries is closer.